Foreign Policy Decision-Making in China: Key Features of the Reforms since the 18th National Congress of the CPC - I. Denisov (Международная аналитика, 2018)
Xi Jinping’s diplomacy relies on certain institutional changes related to the foreign policy decision-making process. National Security Commission (NSC) was established at the 3rd Plenary Session of the 18th Central Committee in November 2013. The paper analyzes the rationale behind this decision, personal composition and main tasks of the NSC. The author argues that further evolution of the National Security Commission does not exclude its transformation into a dual party-state institution in charge of foreign policy and national security. This move will reshape the structure of power distribution in PRC.